2018
DOI: 10.1111/pedi.12675
|View full text |Cite|
|
Sign up to set email alerts
|

The prognosis for glycemic status among children and youth with obesity 2 years after entering a weight management program

Abstract: Prediabetes presents significant morbidity in children with obesity. Family-based lifestyle interventions might delay prediabetes progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…A recent publication of NHANES (1999–2016) found that 25.5% of US youth (10.6 million in 2016) would meet the screening criteria based upon the ADA guidelines 37 . In the NHANES study, in the screen‐eligible population, 4.1% had HbA1c‐defined (≥5.7%) hyperglycaemia, 16.0% had fasting Plasma Glucose‐defined (≥100 mg/dl) hyperglycaemia, whereas 17.9% had hyperglycaemia defined by either HbA1c or fasting plasma glucose, 37 these rates are much lower than when using OGTT criteria, as seen in our study (37.6%), and previously published studies 33–36 . Though HbA1c is a quicker and cheaper test, OGTT is more cost‐effective to screen for paediatric dysglycaemia, with 100% effectiveness (proportion of cases identified) and efficiency (cost/case identified) at $390/case, while HbA1c was the least effective (ranges, 7%–32% and $938–$3370/case) 38 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent publication of NHANES (1999–2016) found that 25.5% of US youth (10.6 million in 2016) would meet the screening criteria based upon the ADA guidelines 37 . In the NHANES study, in the screen‐eligible population, 4.1% had HbA1c‐defined (≥5.7%) hyperglycaemia, 16.0% had fasting Plasma Glucose‐defined (≥100 mg/dl) hyperglycaemia, whereas 17.9% had hyperglycaemia defined by either HbA1c or fasting plasma glucose, 37 these rates are much lower than when using OGTT criteria, as seen in our study (37.6%), and previously published studies 33–36 . Though HbA1c is a quicker and cheaper test, OGTT is more cost‐effective to screen for paediatric dysglycaemia, with 100% effectiveness (proportion of cases identified) and efficiency (cost/case identified) at $390/case, while HbA1c was the least effective (ranges, 7%–32% and $938–$3370/case) 38 .…”
Section: Discussionmentioning
confidence: 99%
“…33,34 This is similarly demonstrated in international populations where the estimated prevalence of dysglycaemia in youth with overweight/obesity was ~40% when screened by OGTT and HbA1c. 35,36 To date, there is limited evidence to guide screening for dysglycaemia based on the number of diabetes risk factors. Our data suggest that the presence of one risk factor besides overweight/obesity is sufficient to merit screening for dysglycaemia, supporting the ADA recommendation.…”
Section: Ogtt-derived Insulin Sensitivity and β-Cell Function And The...mentioning
confidence: 99%
See 1 more Smart Citation
“…In children and adolescents, obesity is associated with high blood pressure and abnormal fasting glucose, dyslipidemia, obstructive sleep apnea, depression, and low quality of life in general. (7)(8)(9). In addition to chronic health diseases, obesity can result in increased mortality among adults (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…In an article by Al Khalifah et al, the second affliation listed for Reem Al Khalifah was incorrect. Reem Al Khalifah is affiliated to the Department of Pediatrics, McMaster University, Hamilton, Canada and the Department of Pediatrics, King Saud University, Riyadh, Saudi Arabia.…”
mentioning
confidence: 99%